Deflected mode and kinematic characteristics of the upper part of the earth’s crust in the area of the Michurinsk deposit (Kirovograd ore area) of the Ukrainian Shield - Mychak, S.V. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2012)
The results of the tectonophysical research carried out in 2010 in the central part of the Ukrainian shield near the Michurinsk uranium deposit are given in this article. The internal structure and stress-strained state of the Earth’s crust have been investigated by the results of the structural and paragenetic fracturing analysis as well as the stress fields by the data of measurements of the fault slip. It was established that the ore-forming phase of deformation within the deposit was the Bobrinetsk-Zhivanovsk shear-thrust one during which a crack separation and extension structures were formed. The redistribution of the ore substance occurred in the Subbotsk-Moshorinsk and Korsun-Novomirgorod stages.